(untitled) (Altre Modernità, 2019)
Svetlana Aleksievič, Tempo di seconda mano. La vita in Russia dopo il crollo del comunismo (Milano, Bompiani, 2018, 777 pp. ISBN 978-88-452-9753-3) di Francesca Volpi